PENGGUNAAN ANALISIS REGRESI LOGISTIK UNTUK MENGANALISIS PERILAKU DAN FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BACA PENGUNJUNG BADAN PERPUSTAKAAN PROPINSI JAWA TIMUR - Kusrini, Dwi Endah; Puspitasari, Dwi (MATEMATIKA, 2006)
This research aim is to know factors and behavior influencing enthusiasm read  Library  visitor Province East Java (Baperpus) by using primary data obtained from survey as much 340 visitor. Method used in this research is Logistic Regression Analysis where the respon variable  is level enthusiasm read visitor ( 1=high, 2= low), while the prediktor variables are visitor behaviors and characteristics variable and got result that there is dependency which signifikan between three variable that is visitor education variable, visit time and visitor work. There no dependency which signifikan between three variable that is between visitor age variable, visitor work and frequency to visit  Baperpus. There no dependency which signifkan between three variable that is between visitor age variable, work and time reside in Baperpus. While based on the model which is formed by Logistic Regression Analysis that one who come when morning with frequency  visit to Baperpus less than once within a week and time reside in Baperpus less than one clock have opportunity of enthusiasm read high equal to 0,19. While one who come when daytime with frequency pay a visit to Baperpus 1-2 times within a week and time reside in Baperpus 1-2 clock have opportunity of enthusiasm read high equal to 0,61. One who come when morning with frequency visit to Baperpus less than once within a week and old reside in Baperpus 2-3 clock have opportunity of enthusiasm read high equal to 0,275 and one who come when daytime with frequency visit to Baperpus 1-2 times within a week and time reside in Baperpus 2-3 clock have opportunity of enthusiasm read high equal to 0,57.